Learning Fun With Games Kahoot For Elementary School Students Grade 1 - Uly, Hawu Yogia Pradana (Universitas Muhammadiyah Sidoarjo, 2023)
Teaching and mentoring students in grade 1 SD is a big challenge for teachers. These constraints are felt by the teacher during the learning process. The difficulty in organizing students to follow and understand the lessons given so that not a few teachers use unique media so that students can be interested in the material that has been given. One example of manual learning media that teachers do in introducing letters, numbers, and objects is still using stickers or objects sold in the market. manual learning is good enough, but it does not rule out boredom and lack of responsiveness from students. The development of technology today is very good and has even become something that is very much needed, be it the use of social media, games, or other things. One of the features that kids usually like is Games. Therefore, I try to be able to combine the use of technology, especially learning media by using a laptop or headphones to make quizzes or games with the theme of learning using Kahoot to help teachers provide learning with unique media that students like and like. make students more interested and more creative in the learning process.